Grammar snobs are great big meanies eaudiobook A guide to language for fun & spite. - Casagrande, June (Tantor Media, 2006)
Here's some good news for everyone who's ever been bullied into believing they can't speak their own language: The grammar snobs are bluffing. Half the "rules" they use to humiliate others are really just judgment calls and the rest they don't even understand themselves. Grammar Snobs Are Great Big Meanies is a laugh-out-loud funny collection of anecdotes and essays on grammar and punctuation, as well as hilarious critiques of the self-appointed language experts. In this collection of hilarious anecdotes and essays, June Casagrande delivers practical language lessons not found anywhere else, demystifying the subject and taking it back from the snobs. "Casagrande brings a lively approach to her overview of basic grammar."— Booklist " . . . Fraser's reading is robust and articulate, and it fully captures Casagrande's sense of humor and witty repartee. Grammar Snobs Are Great Big Meanies is an excellent and entertaining way of learning, or simply reviewing, the fundamentals of English grammar and punctuation."—Reviewed by Auggie Moore, Large Print Reviews Please note: This is a historical recording. The audio quality represents the technology of the time when it was produced.